iTRAQ-Based Quantitative Proteomic Analysis of the Inhibitory Effects of Polysaccharides from Viscum coloratum (Kom.) Nakai on HepG2 Cells - Yangyang Chai (Scientific Reports, 2017)
Abstract Viscum coloratum (Kom.) Nakai is one of active medicinal plants, and its active components, especially polysaccharides, have been shown to exhibit bioactivity. In this study, we examined the effects of three polysaccharide fractions from Viscum coloratum (Kom.) Nakai on HepG2 cell growth in a dose-dependent manner by using a CCK-8 assay kit. Flow cytometry analysis showed that VCP2 treatment delayed the cell cycle in the G1 phase and induced apoptosis in HepG2 cells, a result possibly due to the increased expression of p21Wafl/Cip1 and Cyclin D and the decreased expression of Cyclin E and CDK4. The increased expression of Bad, Smac and Caspase-3 and the decreased expression of Bcl-XL and XIAP may be some of the reasons for the induction of apoptosis in VCP2-treated HepG2 cells. Through iTRAQ and 2D-LC-MSMS, 113 and 198 differentially expressed proteins were identified in normal and VCP2-treated HepG2 and Caco2 cells. The mRNA and protein levels of Histone H3.1, Cytoskeletal 9 and Vitronectin agreed with iTRAQ proteomic results. GO, pathways and the PPI of differentially expressed proteins were further analyzed. These findings broaden the understanding of the anti-tumor mechanisms of mistletoe polysaccharides and provide new clues for screening proteins that are responsive to polysaccharides.